MODEL OPTIMIZATION ASSIGNMENT AIRCRAFT IN THE ALKI II REGION BKO OF THE SECOND FLEET COMMAND II TO SUPPORT THE TASKS OF THE INDONESIAN NAVY - Mardi Winoelyo; Chairul Imron; Adi Bandono; Mohammad Syaifi (JOURNAL ASRO, 2022)
Assignment Marine security operation is an operation where the presence at sea has strategic value for theexistence of national sovereignty and maritime security in Indonesia's national jurisdiction. The threat of securitydisturbances and violations at sea in the form of fishing theft, theft of timber and other natural resources as wellas encroachment on territorial boundaries by foreign ships requires the presence of the Indonesian Navy PatrolElements (Ships and Aircraft) for security. The limited number of TNI AL Patrol Elements and the budgetprovided by the state as well as the need for securing the maritime territory of the Republic of Indonesia hasresulted in the need for thinking about optimizing the assignment of Patrol Ships and Aircraft in the Kamlaoperation sector and placement to their supporting bases, so that the right type and amount and operationalcosts in security. Ships and aircraft carry out patrols in randomly determined sectors. This optimization modelidentifies the related decision variables through open interview discussions, then sets the objective andconstraint functions as an optimization model to be developed. The application of the Goal Programmingmethod can be formulated by determining the decision variables related to the assignment of aircraft where theobjective function is to calculate the maximum radar coverage area in the operating sector and minimizeoperating costs. After optimizing the coverage area, there was an increase of 2.5% and a decrease in operatingcosts of 28%. So that, Mamdani's Fuzzy Logic method is used to determine the output of certain radar coverageareas. In this case, it requires the help of Matlab software on the Fuzzy Inference System (FIZ) toolbox to solvethis problem. Keywords: Maritime Patrol Aircraft, Operating Costs, Goal Programming, Fuzzy Inference System